High Nitrogen Availability Limits Photosynthesis and Compromises Carbohydrate Allocation to Storage in Roots of Manihot esculenta Crantz - Omondi, John Okoth; Lazarovitch, Naftali; Rachmilevitch, Shimon; Yermiyahu, Uri; Sperling, Or (Frontiers in Plant Science, 2019)
Cassava (M. esculenta Crantz), feeding countless people and attracting markets worldwide, is a model for traditional crops that need physiology-based fertigation (fertilization through irrigation) standards in intensive cultivation. Hence, we studied the effects of 10 to 200 mg L-1 nitrogen (N) fertigation on growth and yields of cassava and targeted alterations in their photosynthetic, transpiration, and carbohydrate management. We found that increasing irrigation N from 10 to 70 mg L-1 increased cassava's photosynthesis and transpiration, but supported only the canopy’s growth. At 100 mg N L-1 cassava reached a threshold of sugar in leaves ( 47 mg g-1), began to accumulate starch and supported higher yields. Yet, at 200 mg N L-1, the canopy became too demanding and plants had to restrain transpiration, reduce photosynthesis, decrease carbohydrates, and finally lower yields. We concluded that the phases of cassava response to nitrogen are: 1) growth that does not support yields at low N, 2) productive N application, and 3) excessive use of N. Yet traditional leaf mineral analyses fail to exhibit these responses, and therefore we propose a simple and inexpensive carbohydrate measurement to guide a precise use of N.